Legal Gaps in the Supervision and Practice of Traditional and Non-Medical Alternative Medicine - Ronny Sutanto; Hilda Muliana; Sabda Wahab (Universitas Katolik Soegijapranata Semarang, 2026)
Traditional medicine and non-medical alternatives remain a significant healthcare choice for the Indonesian public despite continuous advancements in modern medical technology. Data from the 2018 Basic Health Research (Riskesdas) indicates that 31.4% of the population still utilizes these services, reflecting enduring trust in local wisdom-based healing practices. However, this high public demand is not matched by an adequate legal and supervisory framework. Many traditional practitioners operate without official licenses, ethical standards, or state oversight. This study aims to (1) analyze positive legal arrangements governing the supervision of traditional and non-medical alternative practices, (2) identify regulatory gaps between legal norms and empirical practices, and (3) formulate an integrated legal protection framework for patients. Employing a normative juridical approach with statutory and conceptual lenses, legal materials were analyzed through a three-stage qualitative process: inventory and classification of regulations, interpretive legal reasoning, and constructive synthesis to develop a patient protection model. Findings reveal that although Law No. 17 of 2023 legally recognizes traditional health services, implementation remains weak due to limited socialization, fragmented supervision, and the absence of specific legal accountability mechanisms. Patient protection is currently partial and non-integrated. The study recommends regulatory harmonization, establishment of a specialized supervisory institution, mandatory practitioner certification, digital promotion oversight, and a pluralistic legal approach that accommodates local wisdom while ensuring patient safety..Abstrak: Pengobatan tradisional dan alternatif non-medis masih menjadi pilihan signifikan masyarakat Indonesia meskipun kemajuan teknologi medis terus berkembang. Data Riskesdas 2018 menunjukkan bahwa 31,4% masyarakat masih memanfaatkan layanan ini, mencerminkan kepercayaan yang kuat terhadap metode penyembuhan berbasis kearifan lokal. Namun, tingginya permintaan masyarakat tidak diimbangi oleh kerangka hukum dan pengawasan yang memadai. Banyak pelaku pengobatan tradisional beroperasi tanpa izin resmi, standar etika, maupun pengawasan negara. Penelitian ini bertujuan untuk (1) menganalisis pengaturan hukum positif terkait pengawasan praktik pengobatan tradisional dan non-medis, (2) mengidentifikasi kesenjangan regulasi antara norma hukum dan praktik empiris, serta (3) merumuskan kerangka perlindungan hukum terintegrasi bagi pasien. Menggunakan pendekatan yuridis normatif dengan perspektif peraturan perundang-undangan dan konseptual, bahan hukum dianalisis melalui proses kualitatif tiga tahap: inventarisasi dan klasifikasi regulasi, penalaran hukum interpretatif, dan sintesis konstruktif untuk membangun model perlindungan pasien. Temuan menunjukkan bahwa meskipun UU No. 17 Tahun 2023 secara hukum mengakui layanan kesehatan tradisional, implementasinya masih lemah akibat sosialisasi terbatas, pengawasan terfragmentasi, dan belum adanya mekanisme pertanggungjawaban hukum spesifik. Perlindungan pasien saat ini bersifat parsial dan tidak terintegrasi. Penelitian merekomendasikan harmonisasi regulasi, pembentukan lembaga pengawas khusus, sertifikasi wajib bagi praktisi, pengawasan promosi digital, serta pendekatan pluralisme hukum yang mengakomodasi kearifan lokal sembari menjamin keselamatan pasien